This moment is your life (and so is this one) : a fun and easy guide to mindfulness, meditation, and yoga - Gates, Mariam (Dial Books, 2018)
Presents tweens and teens with a hands-on guide to mindfulness, meditation, breathing, and yoga. Includes step-by-step directions, colorful artwork, and simple exercises.